Antibacterial Activity Test of Cinnamomum burmannii Solution in Inhibiting the Growth of Aeromonas hydrophila Bacteria - Lilis Cahaya Septiana; Iesje Lukistyowati; Morina Riauwaty (Department of Aquaculture, Faculty of Fisheries and Marine Universitas Riau, 2024)
Aeromonas hydrophila bacteria that cause MAS (Motile Aeromonas Septicemia) disease. Cinnamon contains essential oils, tannins, saponins, flavonoids and phenols. The active compounds of cinnamon essential oil were cinnamaldehyde and cinnamic acid that can inhibit the growth of bacteria. The research was carried out from March to July 2022 at the Laboratory of Fish Parasites and Diseases, Faculty of Fisheries and Marine, Universitas Riau, Pekanbaru. This study aimed to determine the sensitivity of Cinnamomum burmannii in inhibiting the growth of Aeromonas hydrophila bacteria, Minimum Inhibitory Concentration (MIC), and Lethal Dose (LD50) concentration of C. burmannii solution against Cyprinus carpio by immersion technique for 24 hours. The research method used was an experimental method using the Kirby Bauer disc method with concentrations of 100%, 90%, 80%, 70%, 60%, 50%, 40%, 30%, 20%, 10%, 9%, 8%, 7%, 6%, 5%, 4%, 3%, 2%, and 1%. The results shown that the sensitivity of the C. burmannii solution to A. hydrophila bacteria ranged from 22.60 mm to 6.67 mm. The MIC value at a concentration of 4% was determined as the average number of bacterial colonies 143 CFU/mL. The LD50 value of C. burmannii solution against Cyprinus carpio by immersion for 24 hours was 3.64%. Based on the data abtain, it can be concluded that C.burmannii is able to inhibit the growth of A.hydrophila bacteria.